Evaluating Federal and Provincial Solvency Standards in Canada - Nielson, Norma L. (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2009)
This article benchmarks solvency supervisory system for the federal and provincially-licensed companies who write insurance in Canada against/The IAIS Common Structure for the Assessment of Insurer Solvency/. The federal regulator (OSFI) is the only one with statutory authority that provides both sufficient power and flexibility to be considered as meeting the core principles of IAIS. At the provincial level, the insurance supervisory system in some provinces falls short of the international standards to varying degrees and, by extension, the practices of the federal insurance regulator. Alberta, British Columbia, and Québec are not far behind. All other Canadian provinces exhibit extensive deficiencies when compared against international standards.